201k views
4 votes
If f(x) = -x^2 +5z and g (x) = 2x-4 find

User AngelGris
by
5.3k points

1 Answer

3 votes

Answer:

1) x=√−y+5z or x=−√−y+5z

2) g=2x-4/x

Explanation:

explanation for first problem:

Let's solve for x.

y=−x^2+5z

Step 1: Flip the equation.

−x^2+5z=y

Step 2: Add -5z to both sides.

−x^2+5z+−5z=y+−5z

−x^2=y−5z

Step 3: Divide both sides by -1.

−x^2

−1

=

y−5z

−1

x2=−y+5z

Step 4: Take square root.

x=√−y+5z or x=−√−y+5z

explanation for problem 2:

Let's solve for g.

gx=2x−4

Step 1: Divide both sides by x.

gx/x = 2x-4/x

g=2x-4/x

User RachelSunny
by
4.6k points